Impact of supervised physical activity as adjunctive therapy on functional capacity and NT-pro BNP in patients with negative-reactivity test pulmonary hypertension related to congenital heart disease patient in Saiful Anwar Hospital Malang : A preliminary study - Setyowati, Danti Utami; Martini, Heny; Prasetya, Indra; Tjahjono, Cholid Tri; Yogibuana, Valerinna (Universitas Brawijaya, 2025)
Background: Appropriate levels of physical activity (PhA) provide health benefits to patients with chronic diseases, including patients with pulmonary hypertension-related to congenital heart disease (CHD-PH), representing around 4-10% of all PH patients. Objective: The purpose of this analysis was to determine the benefits and effectiveness of PhA as an additional therapy to optimal medication vs. control group on the functional capacity and N-terminal prohormone of B-type natriuretic peptide (NT-pro BNP) in patients with inoperable CHD-PH. Methods: A clinical preliminary study was conducted with 26 consecutive patients in stable condition before the study. Each patient was educated about the benefits of PhA and efficacy parameters of the six-minute walking distance (6MWD) and NT-Pro BNP levels have been evaluated at baseline and after 12 weeks. Results: The study included participants aged 33 ± 11 years, 84% of whom were female. All patients tolerated PhA without severe adverse events. Patients significantly improved the mean 6MWD compared to baseline by 382.9 ± 64.7 (p=0,000) and 318.3 ± 74 (p=0,041) meters after 12 weeks (training vs. control group). Ln NT-pro BNP improved significantly in the training group (p=0,002). There were no differences at week 12 in the delta 6MWD and NT-pro BNP levels, with all P values >0,05. Likewise, there is no correlation between the two variables Conclusions: PhA as an add-on to medical therapy may enhance work capacity and other prognostic relevant parameters in patients with inoperable CHD-PH. However, further larger, multi-center randomized controlled trials, is warranted to validate these preliminary findings